2001
DOI: 10.1366/0003702011951263
|View full text |Cite
|
Sign up to set email alerts
|

New 224 nm Hollow Cathode Laser-UV Raman Spectrometer

Abstract: We have developed an optimized high-throughput UV Raman spectrometer that utilizes a simple, inexpensive new 224.3 nm hollow cathode laser. This quasi-continuous wave (CW) 224.3 nm laser can be used to detect sub-ppm concentrations of aromatic and polycyclic aromatic hydrocarbons in aqueous solutions. This excitation is also useful for studying aromatic amino acids in proteins. We demonstrate the utility of this spectrometer to study the environments of tyr and trp in horse heart myoglobin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Both near infrared (NIR) and deep UV laser (224-266 nm) excited micro-Raman spectroscopic strategies have been proposed for the search for life on Mars, in particular the detection of bi-molecules [32][33][34][35] . The NIR excited Raman spectra have minimum fluorescence from bio-molecules and provide molecular fingerprints of bio-molecules as well as of the substrate.…”
Section: Astrobiological Considerationsmentioning
confidence: 99%
“…Both near infrared (NIR) and deep UV laser (224-266 nm) excited micro-Raman spectroscopic strategies have been proposed for the search for life on Mars, in particular the detection of bi-molecules [32][33][34][35] . The NIR excited Raman spectra have minimum fluorescence from bio-molecules and provide molecular fingerprints of bio-molecules as well as of the substrate.…”
Section: Astrobiological Considerationsmentioning
confidence: 99%
“…Asher [2] [3] showed that natural materials did not fluoresce below a wavelength about 270nm, independent of the excitation wavelength. This was further proven in many subsequent publications such as Nelson [4], Sparrow [5], Wu [6], and many others. When excitation occurs below about 250nm, a fluorescence-free region exists above the laser wavelength in which to observe Raman spectra.…”
Section: Introductionmentioning
confidence: 61%
“…Asher has shown that the wavelength range of fluorescence emission from organic materials is generally longer than 260 nm. [22][23][24][25] This advantage was further proven subsequent publications by Nelson [26], Sparrow [27], Wu [28], and many others. The concept of using fluorescence to detect threat agents or organisms by monitoring fluorescent tags, [29,30] or degradation products [31,32], is well established in the literature.…”
Section: Fluorescence Applications To Surface Analysismentioning
confidence: 81%